Distinguishing Between Transfer Pricing, Transfer Mispricing, and Trade Mis Invoicing: Implications for Indonesia’s Fiscal Resilience - Sahat Parlindungan Simarmata (Cakrawala Repositori IMWI)
The erosion of the multinational tax base is not only related to transfer pricing, but also transfer mispricing and trade mis invoicing which have different normative characteristics and policy implications. PMK 172/2023 and PMK 136/2024 mark a shift in tax base protection from the fairness testing of affiliate transactions towards a global minimum tax architecture. This article analyzes the conceptual differentiation of the three terms and explains how the two PMKs complement each other in dealing with the erosion of the tax base and strengthening Indonesia's fiscal resilience. The research used a qualitative approach in the form of a conceptual study of the latest Indonesian tax regulations and journal literature and academic reports 2016–2026 on transfer pricing, base erosion and profit shifting, and Global Anti-Base Erosion Rules (GloBE). Transfer pricing is a legitimate practice as long as it meets the arm's length principle; Transfer mispricing is an aggressive irregularity that shifts profits to a low-tax jurisdiction; and trade mis invoicing is the manipulation of trade documents related to illicit financial flows. PMK 172/2023 functions as a micro instrument to test the fairness of affiliate transactions, while PMK 136/2024 is a macro instrument through IIR, UTPR, and QDMTT to ensure an effective tax rate of at least 15 percent. All three concepts cannot be treated equally. The protection of Indonesia's tax base requires clarity of terminology, supervision of affiliate transactions, inter-agency coordination, and readiness for compliance with the GloBE regime.